Perancangan Akademi Tari Dengan Konsep High Technology di Dago Bandung, Jawa Barat - Sopian, Wahju; Endangsih, Tri; Iskandaria, Harfa (MAESTRO, 2020)
ABSTRACT As time passes by people are more depending on technology also leaving behind traditional culture and legacy from Indonesia traditional culture, especially the art of traditional dance and other kind of dance that exist in Indonesia, demand upon the art of dance has also decreased within the times. To solve this problem a dance academy will be designed with high technology concept in bandung to keep up with the times and also increase the demand for Indonesia’s traditional dances, the dance academy design is facilitated with high technology based system as a supporting system such as infographic board, academy access, voice recognition command, touch screen dance hall to attract demand for non local civilian so the dance academy will be much more interesting and people can learn the art of dance each other. Keywords : High Technology Architecture, Academy, Bandung, Dance Art